Heparanase influences expression and shedding of syndecan-1, and its expression by the bone marrow environment is a bad prognostic factor in multiple myeloma - Mahtouk, Karène; Hose, Dirk; Raynaud, Pierre; Hundemer, Michael; Jourdan, Michel; Jourdan, Eric; Pantesco, Veronique; Baudard, Marion; De Vos, John; Larroque, Marion; Möhler, Thomas; Rossi, Jean-Francois; et al. (Blood, 2007)
The heparan sulfate (HS) proteoglycan, syndecan-1, plays a major role in multiple myeloma (MM) by concentrating heparin-binding growth factors on the surface of MM cells (MMCs). Using Affymetrix microarrays and real-time reverse transcriptase-polymerase chain reaction (RT-PCR), we show that the gene encoding heparanase (HPSE), an enzyme that cleaves HS chains, is expressed by 11 of 19 myeloma cell lines (HMCLs). In HSPE(pos) HMCLs, syndecan-1 gene expression and production of soluble syndecan-1, unlike expression of membrane syndecan-1, were significantly increased. Knockdown of HPSE by siRNA resulted in a decrease of syndecan-1 gene expression and soluble syndecan-1 production without affecting membrane syndecan-1 expression. Thus, HPSE influences expression and shedding of syndecan-1. Contrary to HMCLs, HPSE is expressed in only 4 of 39 primary MMC samples, whereas it is expressed in 36 of 39 bone marrow (BM) microenvironment samples. In the latter, HPSE is expressed at a median level in polymorphonuclear cells and T cells; it is highly expressed in monocytes and osteoclasts. Affymetrix data were validated at the protein level, both on HMCLs and patient samples. We report for the first time that a gene's expression mainly in the BM environment (ie, HSPE) is associated with a shorter event-free survival of patients with newly diagnosed myeloma treated with high-dose chemotherapy and stem cell transplantation. Our study suggests that clinical inhibitors of HPSE could be beneficial for patients with MM.
Gesehen am 11.02.2022